SYNTAX OBJECTS OF AMHARIC SENTENCES - Berhanu Asaye Agajie (JURNAL ILMIAH BAHASA DAN SASTRA, 2020)
The objective of the study was to examine the Syntactic Object representations found within Amharic sentences classified by their structure. A descriptive analysis was employed to interpret the sentence structures. The data were collected from the native speakers of Awi people (9 males, 7 females) based on their day today outgoing acts, and from different texts. By purposive sampling, 20 sentences were selected, arranged, and described. The method of data analysis employed in this study was Labeling Algorithm {XP, YP}. By modifying SO (raising XP) there exists only one and at least two visible Verbal heads. Results indicated that sentences in terms of their forms, forming Syntactic Object representations they contain were different. On the other hand, each sentence types share Syntactic Object representations that include Noun Phrase (NP), Verb Phrase (VP), Determiner Phrases (DPs) Prepositional phrase (PP), Adverbial Phrase (ADVP), and Adjectival Phrase (AP). Finally, the study recommended a further research how labeling Algorithm {XP, H} and {X, Y} works to describe the label of Syntactic Object representations found within sentences in Awgni.